2014
DOI: 10.21897/rmvz.120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the physicochemical and functional properties of Colombian bee pollen

Abstract: Objective. To establish current knowledge about Colombian bee-pollen from a point of view nutritional and functional, contributing towards creating national technical standards and the identification of chemical differentiation factors for further researches. Material and methods. One hundred ninety-six samples of dried bee pollen were collected in the center region of Colombia known as Cundi-boyacense high plateau, where nearly 90% of total bee pollen production is concentrated in this country. Performed phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 14 publications
7
41
0
2
Order By: Relevance
“…Zinc (Zn) contents were slightly lower (2.9-4.3 mg/100 g) than those found in samples collected in the same Brazilian state (3.7-8.2 mg/100 g) (Carpes et al, 2009) but were similar to those reported by Fuenmayor et al (2014) for samples from Colombia (2.6-5.3 mg/100 g). Samples 1 and 5 are "source foods" of Zn under the ANVISA classification system (Brasil, 2005;Brasil, 2012).…”
Section: Mineral Compositionsupporting
confidence: 59%
“…Zinc (Zn) contents were slightly lower (2.9-4.3 mg/100 g) than those found in samples collected in the same Brazilian state (3.7-8.2 mg/100 g) (Carpes et al, 2009) but were similar to those reported by Fuenmayor et al (2014) for samples from Colombia (2.6-5.3 mg/100 g). Samples 1 and 5 are "source foods" of Zn under the ANVISA classification system (Brasil, 2005;Brasil, 2012).…”
Section: Mineral Compositionsupporting
confidence: 59%
“…For sunflower pollen, ALA and palmitic acid are observed to be the most abundant FAs (Nicolson & Human, 2013). For Colombian bee pollen, the most abundant FAs were ALA, palmitic acid, and LA (Fuenmayor et al, 2014). In eucalypt pollen, LA was dominant at average concentrations of 2.77-5.81 mg/g (Manning & Harvey, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…It is expected that the content of protein in beebread be similar to bee pollen (about 23.8 g/100 g) (Fuenmayor et al, 2014), since the biochemical process induced by bees is aimed in degrading the outer layer of the pollen grain, without any damage of inner content (Zuluaga et al, 2015).…”
Section: Proteins and Amino Acidsmentioning
confidence: 99%